Nonlinear Pushover Analysis of Seismic Load on Multi-Storey Reinforced Concrete Hospital Building - Siah, Meng Zhe (2016)
Nonlinear pushover analysis is a nonlinear static procedure which is a very useful tool to evaluate the seismic performance of a high-rise building. Malaysia is not situated on actively seismic fault zone, but it is close to plate boundaries and surrounded by highly seismic fault zone countries such as Indonesia and Philippines. Therefore, Malaysia is influenced by both local and global earthquake. However, 50% of selected buildings found are facing concrete deterioration problem caused by seismic force. Institution of Engineers (IEM) Malaysia recommended the adoption of Eurocode to substitute BS 8110 for concrete code of practice in local construction industries. In this research, a 7 story hospital building is modeled and the ground condition is assumed at Ranau, Sabah by SCIA Engineer 15. Nonlinear pushover analysis on SCIA Engineer allows the setting of design parameter by adopting the recommendation of European code. The pushover load is then applied onto the model until the structure reaches its failure point, a pushover curve is plotted by base shear vs. roof displacement to evaluate the seismic performance of this hospital buildings. Furthermore, the study of irregularities of model and the application of braced frame system has been conducted. The results show that negative X direction has the strongest seismic resistance with base shear value 127.90MN. In addition, the existence of irregularity reduces the seismic-resistant capacity of buildings and the braced frame system is capable to improve the seismic performance of buildings.